2015
DOI: 10.1371/journal.pone.0120276
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Stone Protein Predicts Postoperative Infection in Cardiac Surgery Patients Irrespective of Cardiopulmonary Bypass or Surgical Technique

Abstract: IntroductionWe investigated the role of pancreatic stone protein (PSP) in predicting the occurrence of infection in the postoperative course of cardiac surgery patients. Several biomarkers indicating the presence of inflammation and infection are available in the clinical routine; yet, their utility in the postoperative course of patients following cardiac surgery remains uncertain. Moreover, cardiopulmonary bypass, also referred to as “on-pump surgery”, increases the susceptibility to an exaggerated inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…To diagnose infection in patients with a particular pathology/condition After cardiac surgery Endocan [92], CD64 [93], pancreatic stone protein [94] After major surgery Peptidoglycan [95], elastase [96], leptin [84], calprotectin [75], a proliferation-inducing ligand [97], α-2 macroglobulin [89], lipopolysaccharide-binding protein [15] COPD Pentraxin 3 [98] Cirrhosis Interleukin (IL)-6 [72] Trauma IL-10 [99], NT-proCNP [100], P-selectin [101] Catheter-related infections Citrulline [102] Infants with necrotic enterocolitis IP-10 [103]…”
Section: Situation Biomarkermentioning
confidence: 99%
“…To diagnose infection in patients with a particular pathology/condition After cardiac surgery Endocan [92], CD64 [93], pancreatic stone protein [94] After major surgery Peptidoglycan [95], elastase [96], leptin [84], calprotectin [75], a proliferation-inducing ligand [97], α-2 macroglobulin [89], lipopolysaccharide-binding protein [15] COPD Pentraxin 3 [98] Cirrhosis Interleukin (IL)-6 [72] Trauma IL-10 [99], NT-proCNP [100], P-selectin [101] Catheter-related infections Citrulline [102] Infants with necrotic enterocolitis IP-10 [103]…”
Section: Situation Biomarkermentioning
confidence: 99%
“…Additional le 1 (.pdf) Situation Biomarker To diagnose infection in patients with a particular pathology/condition After cardiac surgery Endocan [111], CD64 [112], pancreatic stone protein [113] After major surgery Peptidoglycan [114], elastase [115], leptin [103], calprotectin [94], a proliferation-inducing ligand [116], α-2 macroglobulin [108], lipopolysaccharide-binding protein [ To diagnose speci c types of infection Gram (-) vs Gram (+) Fibrin degradation products [128], lipopolysaccharidebinding protein [123], CD11b [106]…”
Section: Additional Filesmentioning
confidence: 99%
“…Ferrara et al have reported that Reg IIIα can be used as a plasma biomarker of GI graft-versus-host disease in combination with clinical stage and histologic grade to improve risk stratification of patients [22]. The biomarker potential of Reg Iα/Reg IIIα has also been validated for identifying septic complication/infection in patients following a variety of surgical procedures [78,79].…”
Section: Reg Family Proteins As Biological Markers Of Inflammatory/neoplastic Diseasesmentioning
confidence: 99%